The Strategies in Strengthening the Role of Zakat Boards and Institutions in Indonesia - Qurroh Ayuniyyah; Didin Hafidhuddin; Hambari Hambari (Center of Strategic Studies (PUSKAS) BAZNAS, 2020)
This study attempts to formulate strategies in strengthening the role of zakat boards and institutions in Indonesia from the perspectives of three zakat experts and practitioners by employing Analytical Network Process (ANP) method. While the indicators of zakat institutions’ performance measured in this study are based on the National Zakat Indices (abbreviated as NZI), the alternatives of strategy are constructed through study of literatures. This study suggests that among four zakat institutions’ indicators, the reporting of zakat shared the highest portion of the important indicators of amil’s performance, followed by the collection, distribution and management of zakat. Besides that, the study also finds that there are strategies that needs to be given top priorities based on its order including optimizing zakat distribution program, strengthening Information and Technology (IT) system, strengthening zakat regulation, improving database of zakat payers and beneficiaries, strengthening the synergy between zakat boards, institutions and other zakat stakeholders, strengthening human resources and improving socialization as well as education pertaining to zakat and the role of zakat boards and institutions.